Upaya Hukum Verzet terhadap Putusan Verstek - M. Abdul Hakim; Nelli Fauziah (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2024)
In the context of legal case resolution through the processes of verstek and verzet, the decision rendered in a verstek trial is considered a formal and substantive resolution of the case. The defendant who loses in such a trial is not granted the right to refile the case unless they choose to file an objection or verzet. Legal guidelines related to the verzet procedure can be found in Article 129 HIR/153 R.Bg and Supreme Court Circular Letter No. 9 of 1964, which provide explanations regarding various interpretations of verstek. The right to file an objection (verzet) is granted to the defendant or their legal representative, who must have been granted special power of attorney in accordance with Article 123 HIR/147 R.Bg and Article 125 HIR/149 R.Bg. Once a verzet is filed, the judicial process involves a panel of judges who will re-examine the case, summoning all parties involved in the verzet to provide clarification and relevant evidence. In the specific context described, the husband acts as the party filing the objection against the verzet, while the wife is the party objected to, and both are summoned according to applicable legal procedures. This entire process reflects the judiciary's effort to ensure justice and legal certainty in resolving disputes between the involved parties.